2022
DOI: 10.21037/atm-22-51
|View full text |Cite
|
Sign up to set email alerts
|

Network pharmacology and molecular docking analysis reveals the mechanism of asiaticoside on COVID-19

Abstract: Background: Asiaticoside (AS) is a saponin extracted from the traditional Chinese herbal medicine Centella Asiatica, which has the effects of reducing inflammatory infiltration and anti-oxidation in pneumonia and combating pulmonary fibrosis. We hypothesize that AS might have therapeutic potential for the treatment of the coronavirus disease 2019 . With the help of network pharmacology and molecular docking techniques, this study discussed the underlying molecular mechanism of AS in the treatment of COVID-19. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Consistent with our finding, molecular docking revealed that asiaticoside had a high affinity with STAT3 for the treatment of the coronavirus disease 2019 (COVID-19). 51 Altogether, these results demonstrate that CE exerts relevant antiinflammatory properties via a cellular mechanism via inhibiting proinflammatory cytokines and JAK/STAT pathway in LPS-stimulated RAW 264.7 macrophages, a model for atopic dermatitis (Figure 7). Future studies employing specific inhibitors or gene knockdown approaches is needed to validate the proposed molecular mechanisms underlying the effects of CE in AD.…”
Section: Discussionmentioning
confidence: 70%
“…Consistent with our finding, molecular docking revealed that asiaticoside had a high affinity with STAT3 for the treatment of the coronavirus disease 2019 (COVID-19). 51 Altogether, these results demonstrate that CE exerts relevant antiinflammatory properties via a cellular mechanism via inhibiting proinflammatory cytokines and JAK/STAT pathway in LPS-stimulated RAW 264.7 macrophages, a model for atopic dermatitis (Figure 7). Future studies employing specific inhibitors or gene knockdown approaches is needed to validate the proposed molecular mechanisms underlying the effects of CE in AD.…”
Section: Discussionmentioning
confidence: 70%
“…It has been noted that the gene OAS1 is an important gene influencing COVID-19 patients [66][67][68][69][70]. The gene STAT4 is the human transcriptomic factor of COVID-19 [71][72][73].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified some host factors and signaling pathways that are essential for the CoV life cycle ( 7 - 10 ). These include pathways related to cell proliferation and apoptosis, such as the ErbB and hypoxia-inducible factor 1 (HIF-1) pathways, and pathways related to innate immune responses, such as the tumor necrosis factor (TNF), nod-like receptor, and retinoic-acid-inducible gene I (RIG-I) signaling pathways ( 11 , 12 ). Among the factors in these pathways, the HIF-1 signaling pathway factor HIF-1a can mediate hypoxia signaling to inhibit SARS-CoV-2 replication and virion production ( 13 ).…”
Section: Introductionmentioning
confidence: 99%